Low‐Frequency Electronic Noise in Quasi‐2D van der Waals Antiferromagnetic Semiconductor FePS3—Signatures of Phase Transitions. (2nd September 2021) - Ghosh, Subhajit; Kargar, Fariborz; Mohammadzadeh, Amirmahdi; Rumyantsev, Sergey; Balandin, Alexander A.
Abstract: Low‐frequency current fluctuations, i.e., noise, in the quasi‐2D van der Waals antiferromagnetic semiconductor FePS3 with the electronic bandgap of 1.5 eV is investigated. The electrical and noise characteristics of the p ‐type, highly resistive, thin films of FePS3 are measured at different temperatures. The noise spectral density is of the 1/ f ‐type over most of the examined temperature range but reveals well‐defined Lorentzian bulges, and increases strongly near the Néel temperature T N  = 118 K ( f is the frequency). Intriguingly, the noise spectral density attains its minimum at temperature T  ≈ 200 K, which is attributed to an interplay of two opposite trends in noise scaling—one for semiconductors and another for materials with the phase transitions. The Lorentzian corner frequencies reveal unusual dependence on temperature and bias voltage, suggesting that their origin is different from the generation—recombination noise in conventional semiconductors. The obtained results are important for proposed applications of antiferromagnetic semiconductors in spintronic devices. They also attest to the power of the noise spectroscopy for monitoring various phase transitions. Abstract : The authors report on the low‐frequency current fluctuations in the quasi‐2D van der Waals antiferromagnetic semiconductor FePS3 . The noise spectral density attains its minimum at temperature T  ≈ 200 K, which is attributed to an interplay of two opposite trends in noise scaling—one for semiconductors and another for materials with the magnetic phase transitions.